Cost-centric innovations to address water-agriculture nexus challenges in Egypt: research status analysis - Brouziyne, Youssef; Eldeeb, E.; Abdoun, R.; Attar, O.; Moumane, I.; El Bergui, O.; Benaly, M. A.; El Bakali, I.; Ali, A. A.; Ez-zaouy, Y.; Abouabdillah, A.; Harbouze, R.; et al. (EDP Sciences, 2024)
High costs associated with technology adoption can be a barrier against the improvement of water use in agriculture. Therefore, interventions must be not only technically feasible but also financially affordable and accessible to farmers. To understand the current situation of research in low-cost (and cost-effective) water solutions for effective management of agricultural water challenges in Egypt. A total of 19 peer-reviewed papers were obtained from systematic research on various databases, the employed keywords are: "Egypt" AND "irrigation" AND "low cost" OR "low-cost" OR "cost-effective" OR "cost-effective". Based on the analysis of the selected studies, many low-cost technologies and techniques are applied in the Egyptian Delta on-farm levels, such as using low-cost soil moisture sensors attached to a smart monitoring unit operated by Solar Photo Voltaic Cells (SPVC), wireless sensor network in cultivating the potato crop, flexible on-field irrigation, cut-off irrigation, and Pressurized Irrigation Systems. The proposed solutions can help improve water use efficiency, increase crop yields, reduce the cost of irrigation, improve the quality of irrigation water, and promote sustainable agricultural practices. The economic analyses and feasibility studies presented in these papers provide valuable insights for policymakers and stakeholders in making informed decisions about water use and agricultural practices.